Entrepreneurial Passion Psychology- Based Influencing Factors of New Venture Performance - Zhao, Shouzheng; Zhou, Yuqin; Guan, Hai; Xu, Wenhai (Frontiers in Psychology, 2021)
Small and medium-sized enterprises have been the driving force of social economy. As the social formation and the rise of many emerging economies, the domestic economic environment changes dramatically, which makes small and medium-sized enterprises face severe challenges. In the face of the fierce competition environment, how to improve the performance of entrepreneurship and gain competitive advantage is a very important topic in the practical management of entrepreneurs. This exploration is carried out with the entrepreneurial passion and risk taking as the antecedent variable, entrepreneurial performance as the outcome variable, and then work engagement as the mediator. With the entrepreneurs of small and medium-sized enterprises as the research object, questionnaire method is used to carry out empirical research. The empirical analysis results show that entrepreneurial passion has a significant positive impact on work engagement; risk taking has a significant positive impact on work engagement; work engagement has a significant positive impact on entrepreneurship performance; in addition, work engagement has intermediary effect on entrepreneurship passion, risk taking and entrepreneurial performance; the results provide academic and practical implications for entrepreneurs.